32 Medicine for Older People Liaison Service to Acute Surgery Reduces Length of Stay of Older People Living with Frailty. (6th February 2020) - Everett, R; Patel, H
Abstract: Background: Of people admitted to the acute surgical unit (ASU) only 23% of them are aged over 70. However the number of bed days they occupy are disproportionate to this; comprising 48% of the total bed days. The average number of bed days rises exponentially with age, with those aged under 70 averaging less than two days; those aged 80 averaging approximately 4.5 bed days and those aged over 90 approximately 7 bed days. This disparity was recognised and a Medicine for Older People (MOP) liaison team comprising consultant geriatrician and Advanced Clinical Practitioner in Frailty starting working with the acute surgical team in November 2018, initially providing support two days a week, increasing to 5 days in March 2019. Methods: The MOP liaison team meets with the acute surgical team each morning identifying and discussing relevant patients; those identified as living with frailty with associated complexity and uncertainty. This group of patients is then reviewed by the MOP liaison team utilising the principles of the comprehensive geriatric assessment to formulate a person-centred plan. Plans are discussed and coordinated with the surgical, nursing and therapy teams utilising a multi-disciplinary/ multi-professional approach. Results: Length of stay is the main outcome measure and readmissions are monitored. Data on admission length and readmissions was analysed from April 2018 and has continued following commencement of the liaison service. Primary results- Length of stay has reduced from 4.4 to 3.3 days on average for all over 70-year-olds admitted to the ASU team. Whilst admission rates have dropped across all age ranges the biggest reduction in readmissions is among the over 80-year-olds with an almost 50% reduction as opposed to a 33% reduction in the under 70 age group Conclusions: Proactively managing the admissions and discharges of patients with frailty allows them to receive the right care at the right time in their period of crisis and shortens their admissions by approximately 25%.